Treatment of household greywater laden with household chemical products in a multi-chambered anaerobic biofilm reactor. (November 2019) - Khuntia, Himanshu Kumar; Chandrashekar, Sanjana; Chanakya, H.N.
Highlights: Presence of household chemical products in greywater reduced the rates of biodegradation. The population and diversity of microbes in AnBR were mainly influenced by substrate composition and effluent recycling. Effluent recycling in AnBR led to simultaneous enhancement in COD removal and volatile fatty acid dissipation. GW and SS fed AnBR was dominated by species of α-Proteobacteria and δ-Proteobacteria, respectively. Greywater constituents were inhibitory to methanogens. Abstract: Anaerobic treatment of greywater (GW) is challenging due to the presence of recalcitrant household chemical products (HCP) that inhibit the activity and growth of organic pollutant degrading anaerobic microbes. This research attempted to overcome this challenge through a novel, multi-chambered anaerobic biofilm reactor (AnBR) containing fluidized PVC media and packed bed lignocellulosic fiber ( Cocus nucifera ) as biofilm support. The long-term effects of feeding HCP laden GW and effluent recycling on the performance of AnBR were corroborated with the bioconversion data and microbial community dynamics. The results indicated that the composition of wastewater and recycling both determine the rates of COD removal, microbial population, and diversity in AnBR. The inhibitory effects exhibited by GW constituents reduced the COD removal efficiencies by 74–94% in comparison to standard substrates (SS), while simultaneously reducing microbial population and diversity by 30–40%. Effluent recycling in GW and SS fed AnBR enhanced the rates of COD removal from 160 mg/L·day to 214 mg/L·day, and 627 mg/L·day to 3540 mg/L·day respectively, with the selective enrichment of Proteobacteria sp. and Methanogenic sp. The GW fed AnBR was dominated by aromatics degrading species of α -Proteobacteria, Synergistetes, etc., whereas, SS fed AnBR were inhabited by fermentative species of δ - Proteobacteria, Bacteroidetes, etc.